Pengaruh Keadilan Organisasi Dan Leader Member Exchange Terhadap Komitmen Organisasi Pada PT. Eka Karya Graha Flora Sukabumi - Anggia Nurul Safarila; Acep Samsudin; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the effect of organizational justice and leader member exchange (LMX) on organizational commitment at PT. Eka Karya Graha Flora Sukabumi. This study uses descriptive and associative methods using saturated sampling technique for sampling by distributing questionnaires to 88 employees of PT. Eka Karya Graha Flora Sukabumi. The data analysis technique used is validity test, reliability test, multiple linear regression analysis including multiple correlation coefficient test, coefficient of determination test, and hypothesis testing t test and f test. The results of this study indicate that organizational justice on organizational commitment has a significant influence and leader member exchange on organizational commitment also has a significant influence. And the results of the influence of organizational justice and leader member exchange have a positive and significant influence on organizational commitment. Keywords: Organizational Justice; Leader Member Exchange; Organizational Commitment